British railways in transition : the economic problems of Britain's railways since 1914 - Aldcroft, Derek Howard (London ; Melbourne ; New York : Macmillan ; St. Martin's Press, 1968)
The primary aim of this book is to discuss and analyse the economic problems of the railways since 1914.
Includes index.
Includes bibliographical references: p. 266-239.
ne 21/01/2019
Loans
Keywords: Railroads; Railroads and state; Britain